Performance in CAREC countries: Cross-sectional evidence at the firm level - Dina Azhgaliyeva; Ranjeeta Mishra; Naoyuki Yoshino; Kamalbek Karymshakov (Asian Development Bank Institute (ADBI), 2021)
This study aims to examine the impact of infrastructure on firm performance in nine CAREC countries: Afghanistan, Azerbaijan, Georgia, Kazakhstan, the Kyrgyz Republic, Mongolia, Pakistan, Tajikistan, and Uzbekistan. Empirical analysis is based on the enterprise survey for 2009, 2013, and 2019. Infrastructure is measured by the duration of power outages, electricity expenses as the share of total sales, access to broadband internet and efficiency of customs. Firm performance was measured by total sales, share of utilized capacity, dummy variable if firm exports, and the share of export sales. Results indicate that firm performance measured through sales and capacity utilization is negatively affected by the duration of power outages and electricity expenses. Moreover, access to broadband internet significantly increases the total sales and export sales of small firms, while efficiency of customs increases the exporting activities of medium and large firms. These findings underline that for the development of private sector and international trade in CAREC countries, sustainable access to, and quality of, electricity, telecommunications, and customs efficiency are important objectives for government policy.
Keywords: D24; H54; O18; Q48; Q41; 330; central Asia; electricity; telecommunications; infrastructure